2021
DOI: 10.1097/qai.0000000000002579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statin Therapy on Age-Associated Changes in Physical Function Among Men With and Without HIV in the Multicenter AIDS Cohort Study

Abstract: Background: The longer-term risks of statins on physical function among people with HIV are unclear. Methods: Longitudinal analysis of Multicenter AIDS Cohort Study men between 40 and 75 years of age with ≥2 measures of gait speed or grip strength. Generalized estimating equations with interaction terms between (1) statin use and age and (2) HIV serostatus, age, and statin use were considered to evaluate associations between statin use and physical func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A recent study of Erlandson et al 23 analyzed the effects of 96 weeks of rosuvastatin on bone, muscle, and fat in PLWH (147 participants [115 males], 72 receiving rosuvastatin and 75 receiving placebo), and they reported a trend for increased lean body mass in the rosuvastatin arm (0.8% increase versus 0.5% decrease in the placebo arm). Abdo et al 22 determined the association between statin use and age-associated changes in physical function among men with (n = 1048) and without HIV (n = 973) and reported that consistent statin users do not seem to have a major impact on physical function (i.e. gait speed and handgrip strength).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of Erlandson et al 23 analyzed the effects of 96 weeks of rosuvastatin on bone, muscle, and fat in PLWH (147 participants [115 males], 72 receiving rosuvastatin and 75 receiving placebo), and they reported a trend for increased lean body mass in the rosuvastatin arm (0.8% increase versus 0.5% decrease in the placebo arm). Abdo et al 22 determined the association between statin use and age-associated changes in physical function among men with (n = 1048) and without HIV (n = 973) and reported that consistent statin users do not seem to have a major impact on physical function (i.e. gait speed and handgrip strength).…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia has been recently demonstrated to be high prevalent among PLWH 20 , 21 . However, the relationship between statin therapy, skeletal muscle outcomes, and physical function is still unclear, especially among PLWH 22 24 .…”
Section: Introductionmentioning
confidence: 99%